Primary cutaneous cryptococcosis: the importance of early diagnosis - Cacilda da Silva Souza; Maria Hideko Takada; Marcela Vendruscolo Ambiel; Viviane Tiemi Nakai (Sociedade Brasileira de Dermatologia, 2021)
Abstract The species of the Cryptococcus neoformans complex show different epidemiological patterns in the infection of immunosuppressed or immunocompetent individuals, and a common tropism peculiarity for the central nervous system. Primary cutaneous cryptococcosis is a rare clinical entity, with manifestations that are initially restricted to the skin through fungal inoculation, and the absence of systemic disease. The authors report in the present study the case of a 61-year-old immunocompetent man, with a rapidly evolving mucoid tumor on abrasions in contact with bird droppings on the forearm. The early identification of the polymorphic skin manifestations and treatment are crucial for the favorable prognosis of the infection, which can be life-threatening.